Be polite and kind - Meiners, Cheri J., 1957-; Johnson, Meredith (Minneapolis, MN : Free Spirit Pub., 2004)
Demonstrates ways of showing politeness, speaking kindly, using basic courtesies, and respecting the feelings of others. Includes role-playing activities.
Book Links (A.L.A.)
Booklist
School Library Journal
3.0
K-3
K-3
Keywords: Conduct of life -- Juvenile literature; Courtesy -- Juvenile literature; Kindness -- Juvenile literature; Conduct of life; Etiquette; Conduct of life; Etiquette